Minimally Invasive Video-Assisted Surgical Management for Parapharyngeal Metastases From Papillary Thyroid Carcinoma: A Case Series Report - Yu, Shi-Tong; Chen, Wan-Zhi; Xu, De-Bin; Xie, Rong; Zhou, Tao; Yu, Ji-Chun (Frontiers in Oncology, 2019)
Background: Papillary thyroid carcinoma (PTC) is the most prevalent cancer type in the endocrine system. Metastases to parapharyngeal lymph nodes (PPLNs) are rare. Herein, we reported a case series of PTC patients with PPLN metastases operated on by using the minimally invasive video-assisted (MIVA) technique to evaluate the safety and effectiveness of this technique. Method: In this single-institutional study, six consecutive PTC patients with PPLN metastases between January 2012 and July 2018 were enrolled. All PPLNs were managed by the MIVA technique. Result: Six patients (three women and three men) who underwent surgery were enrolled in the current study. The median age of patients was 40.5 years (39–66). Five patients (83.3%) were diagnosed with primary PTC with PPLN metastases, and one patient had PTC recurrence in the PPLNs 17 years after her first PTC surgery. Surgical treatment was successful in all patients, and the median operative time and bleeding volume were 185 (100–280) min and 85 (30–120) ml, respectively. None of the patients experienced post-operative complications except for one patient who experienced dysphagia, which resolved within 3 months. During a median follow-up of 15 months (10–31), none of the patients exhibited recurrence or persistent disease. Conclusion: The MIVA transcervical approach was technically feasible and reliable, with less invasiveness for PTC patients with PPLN metastases. Future studies are needed to accumulate more experience, investigate the indications of the technique, and determine the long-term oncological safety.